PEMBERANTASAN SARANG NYAMUK (PSN) DAN UPAYA PENCEGAHAN DEMAM BERDARAH (DBD) DI DESA GONDOSULI - Khotimah, Husnul; Silowati, Veny; Farisman, Gilva; Hasanah, Viki; Fauzi, Ahmad; Nurjanah, suci (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2024)
Dengue fever (DHF) is caused by the dengue fever virus which spreads from person to person through the blood of the Aedes aegypti mosquito, it is important for people to do 3M namely draining, closing and recycling in order to reduce cases of dengue fever that occur.DHF cases appear every year in Gondosuli Village, Pakuniran subdistrict, one of them is Krajan Hamlet (In Gondosuli Village). The investigation we carried out was good on both sides health centers, health cadres and the community, have found that in the environment in The community is not well maintained so it will become a nest for mosquitoes. The purpose of This program is to prevent dengue cases in 2023, through the Service program Mosquito Nest Eradication. This counseling will be held in December 2023. This counseling design is observational with a sample size of 25 samples or by having each alley represented in observations in Gondosuli Village. In This activity program is divided into 3 stages, namely the implementation stage, the supervision stage larvae, and the implementation stage of the discussion results and the benefits of biopores. Result of This activity has obtained data that there are 10 residents' houses detected positive for mosquito larvae, apart from that, people in general have just drained the bathroom once a week, and after conducting a survey of residents and providing flayer benefits Mosquito Nest Eradication